XVI. Asrın ilk yarısında Divriği Kazası (1519- 1548) - Gülsoy, Ersin (My University, 1991)
unknown
Keywords: Orta Anadolu Bölgesi; Osmanlı İmparatorluğu_Tarih_Genişleme Dönemi; Şehir Tarihleri_Divriği; Tarih; Türkiye